IMPLEMENTASI ETIKA BISNIS SYARIAH PADA HOME INDUSTRY MAKANAN OLAHAN SAMBAL AYAM SUWIR NILDA DARMIN - Yuniartik Yuniartik; Mayang Rosana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
This study examines the implementation of sharia business ethics in Nilda Darmin's Shredded Chicken Sambal Processed Food Home Industry. Sharia business ethics, which are instilled are morality, fairness, honesty, and social responsibility, which are considered crucial for the blessings of businesses and MSMEs in Indonesia. The purpose of this study is to find out how the principles of sharia business ethics such as balance, monotheism, free will, obligations, and Iḥsān) are implemented in all aspects of Nilda Darmin's operations, especially in its best-selling product, shredded chicken sambal, since its establishment in 2020 and halal certification in 2024. This study uses a qualitative research design that is field research with case studies. This study shows that Nilda Darmin consistently implements sharia business ethics in the selection of high-quality halal raw materials, clean production processes, transparent promotions, fair pricing, avoiding usury, as well as Iḥsān treatment of employees and social responsibility initiatives. This implementation is not only limited to ensuring halal and product quality, but also building consumer trust to create a positive impact. The implication is that Islamic business ethics need to be continuously improved through the formalization of financial records and the development of more structured social initiatives.